The Harmonization of the Central and Local Governments Authority: Handling Public Health Emergencies on Coronavirus Disease 2019 - Eki Furqon; Edi Mulyadi (UNIFIKASI : Jurnal Ilmu Hukum, 2020)
The global Covid-19 pandemic has made Indonesia do various ways to reduce the spread of covid-19. Through Government Regulation Number 21 of 2020, the Large-Scale Social Restrictions. The aim of this study is to know the relationship pattern of central and local governments in handling public health emergencies and harmonizing any related laws and regulations. This study used juridical normative method with the statutory approach. The study used the Large-Scale Selection of Social Restrictions policy. The findings revealed the central government as the main policy at the regional level, as a party to determine the type of steps that will be taken in handling public health emergency of Covid-19. The selection of Large-Scale Social Restrictions known as PSBB as the main way to suppress the spread of Covid-19 is based on the Regional Government flexibility. In other words, the local government can immediately oblige to apply PSBB in their regions to see the progression and to act quickly upon it. Thus, the synergy between central and local governments in handling covid-19 is indispensable. In conclusion, the implementation of PSBB in Banten Province, especially in Tangerang Raya, successfully reduce the number of positive cases of Covid-19. However, the delay in the implementation of PSBB in Banten Province makes the spread of covid-19 reach to other areas apart from Tangerang Raya.Pandemi global Covid-19 telah membuat Indonesia melakukan berbagai macam cara untuk menekan angka penyebaran Covid-19. Melalui Peraturan Pemerintah Nomor 21 Tahun 2020 tentang Pembatasan Sosial Berskala Besar, pemerintah pusat memilih untuk menggunakan. Tujuan penelitian ini untuk melihat bagaimana pola hubungan antara pemerintah pusat dan pemerintah daerah dalam hal penanganan kedaruratan kesehatan masyarakat dan mengharmoniskan peraturan perundang-undangan yang berkaitan dengan hal tersebut. Metode penelitian ini yang digunakan yaitu yuridis normatif dengan pendekatan peraturan perundang-undangan, studi kebijakan yang dikaji adalah Pemilihan Pembatasan Sosial Berskala Besar. Hasil penelitian didapatkan bahwa, Pemerintah Pusat sebagai haluan utama kebijakan di tingkat daerah menjadi pihak yang dapat menentukan langkah apa yang akan diambil dalam pengananan kedaruratan kesehatan masyarakat Covid-19. Pemilihan Pembatasan Sosial Berskala Besar (PSBB) sebagai cara utama sebagai penekan penyebaran Covid-19 didasarkan pada keleluasaan Pemerintah Daerah yang dapat langsung berkewajiban melaksanakan PSBB di daerahnya sehingga bisa melihat perkembangan sekaligus bertindak cepat dan sinergitas antara pemerintah pusat dan pemerintah daerah dalam penanganan Covid-19 sangat diperlukan. Penerapan PSBB di Provinsi Banten terutama di Tangerang Raya dapat menekan angka kasus positif Covid-19, namun keterlambatan untuk membuat keseluruhan wilayah di Provinsi Banten melaksanakan PSBB membuat penyebaran Covid-19 di Provinsi Banten mulai merambah ke deaerah-daerah yang lain selain Tangerang Raya.